Analisis Kondisi Fisik Atlet Bulutangkis Putra Usia 13–17 Tahun di PB BBC Waru Sidoarjo - Mathias Carensius Dannis Pospos; Panji Bana; Soni Sulistyarto; Yudi Dwi Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to analyze the physical condition of male badminton athletes aged 13–17 years at PB BBC Waru Sidoarjo. This study employed a quantitative approach using a descriptive research design. The participants consisted of 15 male athletes selected through a total sampling technique. Data were collected using a series of physical fitness tests, including the 30-meter sprint test, push-up test, multistage fitness test, vertical jump test, Illinois agility test, sit-and-reach test, and stork stand test. The data were analyzed using descriptive statistics, including minimum and maximum values, mean, standard deviation, frequency, and percentage. The findings revealed that cardiorespiratory endurance (VO₂max) was predominantly classified as good to very good (93.3%), agility was mostly categorized as good (66.7%), and lower-body explosive power was predominantly classified as good (46.7%). Meanwhile, speed, flexibility, and balance were generally categorized as fair to good. In contrast, upper-body muscular strength and endurance demonstrated the lowest performance, with 53.3% of the athletes classified in the poor category. It can be concluded that the overall physical condition of male badminton athletes aged 13–17 years at PB BBC Waru Sidoarjo is generally in the good category. However, improving upper-body muscular strength and endurance should be prioritized in future training programs to further enhance athletic performance. Keywords: Physical Condition, Badminton, Youth Athletes, Physical Fitness Assessment, Sports Training